Rapid quantitative susceptibility mapping of intracerebral hemorrhage. Issue 3 (5th July 2019) - De, Ashmita; Sun, Hongfu; Emery, Derek J.; Butcher, Kenneth S.; Wilman, Alan H.
Abstract : Background: Quantitative susceptibility mapping (QSM) offers a means to track iron evolution in hemorrhage. However, standard QSM sequences have long acquisition times and are prone to motion artifact in hemorrhagic patients. Purpose: To minimize motion artifact and acquisition time by performing rapid QSM in intracerebral hemorrhage (ICH) using single‐shot echo planar imaging (EPI). Study Type: Prospective method evaluation. Population/Subjects: Forty‐five hemorrhages were analyzed from 35 MRI exams obtained between February 2016 and March 2019 from 27 patients (14 male / 13 female, age: 71 ± 12 years) with confirmed primary ICH. Field Strength/Sequence: 3T; susceptibility‐weighted imaging (SWI) with 4.54‐minute acquisition and 2D single‐shot gradient EPI with 0.45‐minute acquisition. Assessment: Susceptibility maps were constructed from both methods. Measurement of ICH area and mean magnetic susceptibility were made manually by three independent observers. Motion artifacts were quantified using the magnitude signal ratio of artifact‐to‐brain tissue to classify into three categories: mild or no artifact, moderate artifact, or severe artifact. The cutoff for each category was determined by four observers. Statistical Tests: Pearson's correlation coefficient and paired t ‐test using α = 0.05 were used to compare results. Inter‐ and intraclass correlation was used to assess observer variability. Results: Using 45 hemorrhages, the ICH regions measured on susceptibility maps obtained from EPI and SWI sequences had high correlation coefficients for area (R 2  ≥ 0.97) and mean magnetic susceptibility (R 2  ≥ 0.93) for all observers. The artifact‐to‐tissue ratio was significantly higher ( P  < 0.01) for SWI vs. EPI, and the standard deviation for the SWI method (SD = 0.05) was much larger than EPI (SD = 0.01). All observers' measurements showed high agreement. Data Conclusion: Single‐shot EPI‐QSM enabled rapid measurement of ICH area and mean magnetic susceptibility, with reduced motion as compared with more standard SWI. EPI‐QSM requires minimal additional acquisition time and could be incorporated into iron tracking studies in ICH. Level of Evidence: 2 Technical Efficacy Stage: 1 J. Magn. Reson. Imaging 2020;51:712–718.